Strategi dan Metode Dakwah KH. Asep Saifuddin Chalim - Puspita, Reni (Communicator: Journal of Communication, 2024)
In the implementation of da'wah methods in Islamic educational institutions, such as boarding schools, the role of a Kiai (religious leader) is crucial in determining the success of the da'wah process. A Kiai, who leads a boarding school, is expected to possess both intellectual and practical skills in his capacity as a preacher, ensuring that the message of da'wah is delivered effectively, efficiently, and accurately to its intended audience. This assertion raises several research questions: What is the da'wah concept of Dr. KH. Asep Saifuddin Chalim, MA, at Amanatul Ummah Islamic Boarding School in Pacet, Mojokerto? How does he apply this concept? And what challenges are encountered in the application of his da'wah methods? The research addressing these questions employed qualitative methods, focusing on the da'wah approach. Data collection involved descriptive analytical techniques, gathering information in the form of words, images, and documents rather than numbers. This data was obtained through observations, in-depth interviews with key informants, and relevant documentation. The purpose of this approach was to enable the researcher to interpret the collected data comprehensively.